THE INFLUENCE OF THE E-SAMSAT PROGRAM, MOBILE SAMSAT, SAMSAT DRIVE THRU, TAX SOCIALIZATION AND MORAL OBLIGATION PROGRAM COMPIANCE ON MOTOR VEHICLE TAXPAYER COMPLIANCE REGISTERED WITH SAMSAT SUBANG - Dinda Dwi Agista; Icih Icih; Asep Kurniawan (Journal of Taxation Analysis and Review, 2022)
This study aims to determine the factors that influence the compliance of motor vehicle taxpayers either partially or simultaneously. The data used in this study is primary data by distributing questionnaires in the form of google form. The method used in sampling is non-probability sampling method, namely incidental sampling and the number of samples in this study were 200 respondents, who were the people of Subang or in this study the taxpayers of motorized vehicles in Subang Regency. The data was processed using the data quality test method, classical assumption test, multiple regression analysis, and hypothesis testing. The results showed that partially the mobile samsat, Samsat Drive Thru and Moral Obligation variables had a positive and significant effect on motor vehicle taxpayer compliance. While the e-Samsat program variables and tax socialization have no effect on motor vehicle taxpayer compliance. Simultaneously, the results showed that simultaneously the variables of the e-Samsat program, mobile samsat, Drive Thru samsat, tax socialization, and Moral Obligation had an effect on motor vehicle taxpayer compliance.